Does Childhood Psychological Abuse Contribute to Intimate Partner Violence Victimization? An Investigation Using the Childhood Experience of Care and Abuse Interview - LoCascio, Maria (Journal of interpersonal violence, 2021)
Although psychological abuse is recognized as a particularly insidious form of child abuse, research on the impact of this type of abuse related to intimate partner violence (IPV) is scant. This study examined the contribution of childhood psychological abuse to IPV in female victims and non-victims. Furthermore, it investigated the role of cumulative abuse in predicting IPV. The study included 38 women victims of IPV and 40 non-IPV women. All participants were investigated using the Childhood Experience of Care and Abuse Interview (CECA); the Revised Conflict Tactics Scale (CTS2) and the IPV History Interview were used to assess IPV in the last year and lifetime, respectively. Results indicated that psychological abuse was a stronger predictor of IPV than other maltreatment types. Furthermore, dose–response effects of cumulative abuse on IPV are well evidenced. Future research should continue examining impacts of psychological abuse on IPV so as to further inform clinical practice and intervention planning.